50 KILAU UMP volunteers plant 400 trees in Tasik Chini - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
CHINI, 10 September 2022 - A total of 50 KILAU volunteers from Universiti Malaysia Pahang (UMP), comprising students and staff of Next Green Pulp and Papers (NGPP), participated in the Tree Planting Programme in conjunction with the 100 Million Trees Planting Campaign at Tasik Chini, Pahang.